Integrated chemical profiling of Zhi-Zi-Hou-Po decoction by liquid chromatography-diode array detector-time of flight mass analyzer and liquid chromatography-triple stage quadrupole mass analyzer combined with chemometrics. Issue 23 (27th May 2016) - Liu, Yuan; Yang, Gongjun; Feng, Fang
Abstract : An effective strategy using LC-DAD-TOF/MS and LC-MS/MS based chemometrics for identification and difference analysis of herb formulae is proposed. Abstract : Zhi-Zi-Hou-Po Decoction (ZZHPD) is an effective traditional Chinese medicine formula used for treatment of depression. Despite clinical applications for thousands of years, the therapeutic mechanism of ZZHPD remains limited, partly because the chemical composition and the interactions of multi-herbs during co-decoction are unclear. In this study, an effectively integrated method based on liquid chromatography coupled with diode array detector-time of flight mass analyser, liquid chromatography-triple stage quadrupole mass analyser, and chemometrics was developed to identify the compounds in ZZHPD and to reveal the potential physicochemical changes during decoction. 108 compounds in the decoction, which were assigned to corresponding herbs, were elucidated based on the accurate mass of the quasi-molecular ions and fragment ions from the time-of-flight mass analyser and/or their MS/MS behavior. The retention times and UV absorptions of compounds were used to assist in identifying them. Available reference standards were employed for further confirmation. In the positive ion mode, 40 of the compounds were screened by orthogonal partial least squares discriminant analysis as characteristic ingredients to analyze interactions among the herbs. Compared with a single herb, it was found that the concentration of all components in ZZHPD decreased except alkaloids from Magnoliae officinalis . The results indicated that the changes of chemical compositions in the process of multi-herb decoction might be an important material basis for the synergistic efficacy of herb formulae. The research laid a foundation for further exploration of the therapeutic mechanism of ZZHPD. Overall, the study method should be useful for the identification and investigation of multi-herb interaction analysis.